Robust Brain Hyperglycemia during General Anesthesia: Relationships with Metabolic Brain Inhibition and Vasodilation - Bola, R. Aaron; Kiyatkin, Eugene A. (Frontiers in Physiology, 2016)
Glucose is the main energetic substrate for the metabolic activity of brain cells and its proper delivery into the extracellular space is essential for maintaining normal neural functions. Under physiological conditions, glucose continuously enters the extracellular space from arterial blood via gradient-dependent facilitated diffusion governed by the GLUT-1 transporters. Due to this gradient-dependent mechanism, glucose levels rise in the brain after consumption of glucose-containing foods and drinks. Glucose entry is also accelerated due to local neuronal activation and neuro-vascular coupling, resulting in transient hyperglycemia to prevent any metabolic deficit. Here, we explored another mechanism that is activated during general anesthesia and results in significant brain hyperglycemia. By using enzyme-based glucose biosensors we demonstrate that glucose levels in the nucleus accumbens (NAc) strongly increase after iv injection of Equthesin, a mixture of chloral hydrate and sodium pentobarbital that is often used for general anesthesia in rats. By combining electrochemical recordings with brain, muscle, and skin temperature monitoring, we show that the gradual increase in brain glucose occurring during the development of general anesthesia tightly correlate with decreases in brain-muscle temperature differentials, suggesting that this rise in glucose is related to metabolic inhibition. While the decreased consumption of glucose by brain cells could contribute to the development of hyperglycemia, an exceptionally strong positive correlation (r=0.99) between glucose rise and increases in skin-muscle temperature differentials was also found, suggesting the strong vasodilation of cerebral vessels as the primary mechanism for accelerated entry of glucose into brain tissue. Our present data could explain drastic differences in basal glucose levels found in awake and anesthetized animal preparations. They also suggest that glucose entry into brain tissue could be strongly modulated by pharmacological drugs via drug-induced changes in metabolic activity and the tone of cerebral vessels.